2019
DOI: 10.1186/s12887-019-1666-5
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes of glycoprotein B gene among the Indian symptomatic neonates with congenital CMV infection

Abstract: Background Cytomegalovirus [CMV] is a causative agent of congenital infection worldwide and often leads to neurological deficits and hearing loss in newborns. Infants born with symptomatic congenital Cytomegalovirus infection [cCMV] are at significant high risk for developing adverse long-term outcomes. In this study, we look into the sequence variability of surface glycoprotein B [gB] encoding region in newborns with symptomatic CMV infection for the first time in Eastern region of India. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Compared to a single gB genotype infection, mixed gB genotype infections are frequently reported in organ/bone marrow transplant recipients and AIDS patients [105,118,125,128,129,152]. Multiple studies have also demonstrated that mixed infections are able to be transmitted in utero [63,68,[74][75][76][77]109,122,134,137,138,141]. Although there is no established association between single genotype infections and disease outcomes, patients with mixed gB genotype infections have been reported to have faster disease progression or higher viral loads [83,97,102,144].…”
Section: Gbmentioning
confidence: 99%
“…Compared to a single gB genotype infection, mixed gB genotype infections are frequently reported in organ/bone marrow transplant recipients and AIDS patients [105,118,125,128,129,152]. Multiple studies have also demonstrated that mixed infections are able to be transmitted in utero [63,68,[74][75][76][77]109,122,134,137,138,141]. Although there is no established association between single genotype infections and disease outcomes, patients with mixed gB genotype infections have been reported to have faster disease progression or higher viral loads [83,97,102,144].…”
Section: Gbmentioning
confidence: 99%
“…The first five genotypes have been detected in Asia, Europe, and North America. However, their geographic distribution differs: gB1 is the most prevalent genotype in Asia and Egypt [ 6 , 14 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]; gB1 and gB2 are frequently detected in North America [ 39 , 40 , 41 , 42 , 43 , 44 , 45 ]; in South America, the most frequent genotypes were gB1 and gB2 [ 9 , 10 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] whereas gB1, gB2, and gB3 are commonly observed across Europe (with the exception of Serbia where gB4 is the most prevalent genotype) [ 55 , 56 , 57 , 58 , 59 ...…”
Section: Discussionmentioning
confidence: 99%
“…Paradowska et al demonstrated that the gB2 genotype was prevalent in Polish newborns with symptomatic cCMV infection ( 48 , 66 ). However, Sarkar et al ( 17 ) demonstrated that gB1 was the most widespread genotype among Indian neonates with symptomatic cCMV infection. Another two cohorts also confirmed our findings that gB1 was the most common genotype in neonates and infants with symptomatic cCMV infection ( 57 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…cCMV infection contributes more to the permanent disabilities of infants and young children than other congenital diseases ( 14 16 ). Neonates with symptomatic CMV infections are at even higher risk for the adverse neurodevelopmental sequelae and proved to be associated with many severe clinical manifestations ( 17 ).…”
Section: Introductionmentioning
confidence: 99%